Polyester resin composition and molding

The polyester resin composition addresses issues of poor separation, flexibility, and mold pollution by incorporating specific components, resulting in improved molding efficiency and stability for small moldings.

JP2025015466APending Publication Date: 2025-01-30UNITIKA LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024113463
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-16
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing polyester resin compositions used for small moldings, such as buttons and zippers, suffer from poor separation, flexibility, shape stability, and longer molding cycles, leading to reduced productivity and mold pollution.

Method used

A polyester resin composition comprising polyethylene terephthalate-based resin, thermoplastic polyester elastomer, layered clay minerals, crystallization accelerator, and release agent, optimized for specific viscosities and proportions, to enhance separation, flexibility, and shape stability while reducing mold pollution.

Benefits of technology

The composition achieves shorter molding cycles, improved separation, flexibility, and shape stability, with reduced mold pollution, suitable for high-temperature environments, and enables monomaterial use in small moldings like buttons, zippers, and fixed rings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015466000001
    Figure 2025015466000001
  • Figure 2025015466000002
    Figure 2025015466000002
  • Figure 2025015466000003
    Figure 2025015466000003
Patent Text Reader

Abstract

To provide a polyester resin composition from which a molding excellent in releasability and flexibility can be obtained.SOLUTION: The polyester resin composition contains 100 pts.mass of a polyethylene terephthalate resin (A), 1.0-12.5 pts.mass of a thermoplastic polyester elastomer (B), 0.5-6.2 pts.mass of a layered clay mineral (C), 0.2-5.0 pts.mass of a crystallization accelerator (D), and 0.1-1.0 pt.mass of a release agent (E). The polyethylene terephthalate resin (A) preferably has an intrinsic viscosity of 0.65-1.15.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester resin composition and a molded article. [Background technology]

[0002] 2. Description of the Related Art It has been known to use unsaturated polyester resins and vinyl ester resins for small molded articles such as buttons and fasteners attached to clothing and the like (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-007812 Summary of the Invention [Problem to be solved by the invention]

[0004] When a polyethylene terephthalate resin is used to obtain a small molded product by injection molding, the molded product has problems such as poor releasability and flexibility, mold contamination, poor shape stability, and a long molding cycle, resulting in poor productivity.

[0005] An object of the present invention is to provide a polyester resin composition which is excellent in releasability, flexibility and shape stability, and which can give a small molded article in a shorter molding cycle. [Means for solving the problem]

[0006] Means of Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that a polyester resin composition having a specific formulation can solve the above problems, thereby completing the present invention. That is, the gist of the present invention is as follows.

[0007] (1) A polyester resin composition comprising 100 parts by mass of a polyethylene terephthalate resin (A), 1.0 to 12.5 parts by mass of a thermoplastic polyester elastomer (B), 0.5 to 6.2 parts by mass of a layered clay mineral (C), 0.2 to 5.0 parts by mass of a crystallization accelerator (D), and 0.1 to 1.0 part by mass of a release agent (E). (2) The polyester resin composition according to (1), wherein the polyethylene terephthalate-based resin (A) has an intrinsic viscosity of 0.65 to 1.15. (3) A molded article comprising the polyester resin composition of (1) or (2). (4) A molded body according to (3) having a mass of 15 g or less. (5) A button, hook, fastener or fastening ring obtained by molding the polyester resin composition according to (1) or (2). (6) Use of buttons, hooks, zippers or fastening rings as defined in (5) above on textile products made of polyethylene terephthalate-based fibers. (7) (5) Textile products made of polyethylene terephthalate-based fibers having buttons, hooks, zippers or fastening rings. Effect of the Invention

[0008] The polyester resin composition of the present invention can obtain small molded articles having excellent mold releasability and flexibility even when a polyethylene terephthalate resin is used. In addition, the molded articles obtained by molding the polyester resin composition of the present invention can suppress mold contamination, shorten the molding cycle, and have excellent shape stability. In addition, in products such as clothing, carpets, and car mats containing polyethylene terephthalate fibers, the composition can be used for small molded articles such as buttons, fasteners, hooks, and fixing rings, thereby enabling mono-materialization of the products. Furthermore, the buttons and the like containing the polyester resin composition of the present invention have excellent dimensional stability even in environments exposed to high temperatures, such as a washing and drying machine or an iron. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below. The polyester resin composition of the present invention (sometimes simply referred to as "resin composition") contains 100 parts by mass of a polyethylene terephthalate resin (A), 1.0 to 12.5 parts by mass of a thermoplastic polyester elastomer (B), 0.5 to 6.2 parts by mass of a layered clay mineral (C), 0.2 to 5.0 parts by mass of a crystallization accelerator (D), and 0.1 to 1.0 part by mass of a release agent (E).

[0010] The polyethylene terephthalate resin (A) constituting the present invention preferably has an intrinsic viscosity of 0.65 to 1.15, more preferably 0.70 to 1.10. If the intrinsic viscosity is less than 0.65, the flexibility of the polyester resin composition may decrease, while if the intrinsic viscosity exceeds 1.15, the flowability may decrease, resulting in deterioration of moldability and releasability. The intrinsic viscosity can be measured using an equal weight mixture of phenol and tetrachloroethane as a solvent.

[0011] The polyethylene terephthalate resin (A) is a polyester resin containing ethylene terephthalate units as a main constituent component, and may be copolymerized with other components. Other components include dicarboxylic acids such as saturated aliphatic dicarboxylic acids exemplified by oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, tetradecanedicarboxylic acid, hexadecanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornanedicarboxylic acid, and dimer acid, or ester-forming derivatives thereof, and unsaturated fatty acids exemplified by fumaric acid, maleic acid, and itaconic acid. and aromatic dicarboxylic acids or ester-forming derivatives thereof, such as orthophthalic acid, isophthalic acid, terephthalic acid, 5-(alkali metal)sulfoisophthalic acid, diphenic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 15-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenecarboxylic acid, 4,4'-biphenyldicarboxylic acid, 4,4'-biphenylsulfonedicarboxylic acid, 4,4'-biphenyletherdicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, pamoic acid, and anthracenedicarboxylic acid, or ester-forming derivatives thereof.

[0012] Examples of polyvalent carboxylic acids other than the above dicarboxylic acids include ethanetricarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, pyromellitic acid, trimellitic acid, trimesic acid, 3,4,3',4'-biphenyltetracarboxylic acid, and ester-forming derivatives thereof.

[0013] Other components, such as diol components, include 1,2-propylene glycol, 1,3-propylene glycol, diethylene glycol, triethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, and 1,4-cyclohexanediethanol. and aromatic glycols such as hydroquinone, 4,4'-dihydroxybisphenol, 1,4-bis(β-hydroxyethoxy)benzene, 1,4-bis(β-hydroxyethoxyphenyl)sulfone, bis(p-hydroxyphenyl)ether, bis(p-hydroxyphenyl)sulfone, bis(p-hydroxyphenyl)methane, 1,2-bis(p-hydroxyphenyl)ethane, bisphenol A, bisphenol C, 2,5-naphthalenediol, and glycols obtained by adding ethylene oxide to these glycols.

[0014] The resin composition of the present invention may contain a polyester resin other than the polyethylene terephthalate resin (A). Polyester resin other than polyethylene terephthalate resin may include known thermoplastic polyester, and is not particularly limited.For example, polyalkylene terephthalate such as polytrimethylene terephthalate, polybutylene terephthalate, polycyclohexanedimethylene terephthalate, polyalkylene naphthalate such as polyethylene naphthalate, polybutylene naphthalate, polyhydroxybutyrate, polycaprolactone, polybutylene succinate, polyethylene succinate, polylactic acid resin, polymalic acid, polyglycolic acid, polydioxanone, polypropyllactone, aromatic polyester / polyether block copolymer, aromatic polyester / polylactone block copolymer, polyarylate.Among them, polyethylene naphthalate, polybutylene terephthalate and polylactic acid are preferred.

[0015] The content of the polyethylene terephthalate resin (A) in the present invention is preferably 80 to 95% by mass of the entire resin composition. If the content of the polyethylene terephthalate resin (A) is less than 80% by mass, it may not be suitable for use as a part that requires mono-materialization, such as buttons and zippers in clothing containing polyethylene terephthalate fibers. On the other hand, if the content of the polyethylene terephthalate resin (A) exceeds 95% by mass, it may be undesirable because of reduced releasability and flexibility.

[0016] The polyethylene terephthalate resin (A) in the present invention may be a recycled polyethylene terephthalate resin recycled from used clothes, used bottles, etc. The recycling method may be chemical recycling or material recycling.

[0017] The resin composition of the present invention contains the thermoplastic polyester elastomer (B), and thus has excellent mold releasability, shape stability, flexibility and dimensional stability, and can suppress mold contamination during molding. The thermoplastic polyester elastomer (B) constituting the present invention is a block copolymer consisting of hard segments and soft segments, and is a thermoplastic elastomer having polyester bonds in the molecular chain. For example, there may be mentioned a block copolymer having a high melting point polyester segment as the hard segment and a low melting point polymer segment as the soft segment.

[0018] Here, a high melting point polyester segment is one that has a melting point of 150°C or higher when a high molecular weight polymer is formed only from high melting point polyester segment components, and a low melting point polymer segment is one that has a melting point softening point of 80°C or lower when measured only from low melting point polymer segment components, and typically has a molecular weight of about 400 to 6000.

[0019] The polyesters constituting the high melting point polyester segment include aromatic dicarboxylic acid residues such as terephthalic acid, isophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, bis(p-carboxyphenyl)methane, and 4,4'-sulfonyldibenzoic acid, and ethylene glycol, trimethylene glycol, tetramethylene glycol, pentamethylene glycol, 2,2-dimethyltrimethylene glycol, hexamethylene glycol, octamethylene glycol, decamethylene glycol, cyclohexanedimethanol, p Examples of the high melting point segment include polyesters consisting of a diol residue such as β-xylylene glycol, copolyesters using two or more dicarboxylic acids or two or more diols, polyesters derived from oxyacids such as p-oxybenzoic acid and p-(β-hydroxyethoxy)benzoic acid and their residues, polyetheresters consisting of residues of aromatic ether dicarboxylic acids such as 1,2-bis(4,4'-dicarboxymethylphenoxy)ethane and di(4-carboxyphenoxy)ethane and the above diol residues, and copolyesters combining the above dicarboxylic acids, oxyacids, and diols. In such copolyesters, a small amount of aliphatic dicarboxylic acid residues or aliphatic oxyacid residues may be included. In any case, a high melting point segment having a melting point of 150°C or higher is used. Polytetramethylene terephthalate or polyethylene terephthalate is preferred, and polytetramethylene terephthalate is particularly preferred.

[0020] The low melting point polymer segment constituting the polyester-based thermoplastic elastomer (B) preferably has a melting point or softening point of 80° C. or lower and is in a substantially amorphous state. The molecular weight of the low melting point polymer segment is preferably about 400 to 6000, particularly preferably about 600 to 5000. Specific examples of the low melting point polymer segment include polyoxyalkylene glycols such as polyoxyethylene glycol, polyoxypropylene glycol, polyoxytetramethylene glycol, and polyoxyethylene-polyoxypropylene glycol, and mixtures of these.

[0021] Examples of the low melting point polymer segment include aliphatic polyesters such as polyesters or copolyesters of aliphatic or alicyclic dicarboxylic acids having 2 to 12 carbon atoms and aliphatic or alicyclic diols having 2 to 10 carbon atoms, polyesters or copolyesters of aliphatic lactones having 4 to 10 carbon atoms, and copolyesters of aliphatic or alicyclic dicarboxylic acids, aliphatic or alicyclic diols, and aliphatic lactones. More specific examples include polyethylene adipate, polytetramethylene adipate, polyethylene sebacate, polythineopentyl sebacate, polytetramethylene dodecanate, polytetramethylene azelate, polyhexamethylene azelate, poly-ε-caprolactone, etc.

[0022] As the low melting point polymer segment, the above-mentioned polyoxyalkylene glycol and aliphatic polyester can also be used in combination.

[0023] The polyester-based thermoplastic elastomers, such as polyester-polyether block copolymers using polyoxyalkylene glycol as the low melting point polymer segment and polyester-polyester block copolymers using aliphatic polyester as the low melting point polymer segment, preferably contain 5 to 80% by weight, particularly 15 to 70% by weight of low melting point polymer segments such as polyoxyalkylene glycol and aliphatic polyester, and more preferably have a melt flow rate of 0.1 to 1000 g / 10 min, particularly 1 to 100 g / 10 min at 230°C and a load of 2160 g.

[0024] The polyester thermoplastic elastomer (B) can be produced by a conventional polycondensation method. For example, a method of obtaining a polyester block copolymer by heating an aromatic dicarboxylic acid or its dimethyl ester, a low-melting point segment-forming diol, and a low-molecular weight diol to about 150 to 260°C in the presence of a catalyst to perform an esterification reaction or an ester exchange reaction, and then performing a polycondensation reaction while removing an excess of the low-molecular weight diol under vacuum; a method of obtaining a polyester block copolymer by mixing a bifunctional chain extender that reacts with the terminal groups of the prepolymers with a high-melting point polyester segment-forming prepolymer and a low-melting point polymer segment-forming prepolymer that have been prepared in advance and reacting them, and then maintaining the system at a high vacuum and removing volatile components; a method of obtaining a polyester block copolymer by heating and mixing a high-melting point polyester with a high polymerization degree and lactones, and performing an ester exchange reaction while ring-opening polymerizing the lactones.

[0025] Another example of the polyester-based thermoplastic elastomer (B) is a multiblock copolymer using a low molecular weight liquid crystal compound such as dihydroxy-p-quaterphenyl as the hard segment and the above-mentioned aliphatic polyester as the soft segment. In such a polyester-based thermoplastic elastomer, it is preferable to use one having a Shore A hardness of 90 or less, particularly 85 or less.

[0026] In the present invention, the polyester-based thermoplastic elastomer (B) is contained in the range of 1.0 to 12.5 parts by mass, preferably 3.0 to 10.0 parts by mass, per 100 parts by mass of the polyethylene terephthalate-based resin (A). If it is less than 1.0 part by mass, the effect of improving toughness is poor, and flexibility is reduced, which may cause the product to break. On the other hand, if it exceeds 12.5 parts by mass, hardness is reduced, shape stability is deteriorated, and the product may deform or dimensional stability is reduced. In addition, mold contamination occurs.

[0027] The layered clay mineral (C) used in the present invention is a mineral mainly composed of layered silicate, and can improve heat resistance and processability. In particular, the layered clay mineral (C) is preferably one or more selected from the group consisting of smectite, mica, talc, pyroferrite, vermiculite, chlorite, kaolinite, and serpentine, in that it is easy to improve processability. In terms of versatility, mica, talc, and kaolinite are preferred, and talc is particularly preferred.

[0028] In the resin composition of the present invention, the layered clay mineral (C) is contained in the range of 0.5 to 6.2 parts by mass, preferably 1.0 to 5.5 parts by mass, and more preferably 2.0 to 5.0 parts by mass, per 100 parts by mass of the polyethylene terephthalate resin (A). If it is less than 0.5 parts by mass, the effect of addition is poor, the cooling time is extended, the mold releasability is deteriorated, and the shape stability and dimensional stability are reduced. If it exceeds 6.2 parts by mass, the toughness is reduced and the flexibility is deteriorated.

[0029] Examples of the crystallization accelerator (D) constituting the resin composition of the present invention include ether ester compounds, fatty acid esters, higher fatty acid esters, alcohol esters, polyhydric alcohol esters, glycerin esters, and polyglycerin esters.

[0030] In the resin composition of the present invention, the crystallization accelerator (D) is contained in the range of 0.2 to 5.0 parts by mass, preferably 1.0 to 4.0 parts by mass, based on 100 parts by mass of the polyethylene terephthalate resin (A). If it is less than 0.2 parts by mass, the crystallization accelerator effect is not sufficiently obtained, and a longer cooling time is required, resulting in poor mold releasability. In addition, the shape stability, dimensional stability, and flexibility are poor. On the other hand, if it exceeds 5.0 parts by mass, it causes bleeding out, contaminating the mold, and reducing the quality of the product.

[0031] Specific examples of the release agent (E) used in the present invention include vegetable waxes such as carnauba wax and rice wax, animal waxes such as beeswax and lanolin, mineral waxes such as montan wax, petroleum waxes such as polyethylene wax, paraffin wax, and montanic acid complex ester wax, oil-based waxes such as castor oil and its derivatives, and fatty acids and their derivatives. Among these, paraffin wax is preferably used.

[0032] In the resin composition of the present invention, the release agent (E) is contained in the range of 0.1 to 1.0 parts by mass, preferably 0.2 to 0.7 parts by mass, based on 100 parts by mass of the polyethylene terephthalate resin (A). If it is less than 0.1 part by mass, the release effect is not sufficient, and shape stability and dimensional stability are poor. On the other hand, if it exceeds 1.0 part by mass, there is no problem with release, but the mold is contaminated by bleeding out during molding, and the quality of the product is reduced.

[0033] To the polyester resin composition of the present invention, other conventional additives such as antioxidants, stabilizers, ultraviolet absorbers, colorants, flame retardants, flame retardant assistants, impact modifiers, lubricants, and small amounts of other polymers can be added within the range not impairing the effects of the present invention.

[0034] In the polyester resin composition of the present invention, the above components are preferably uniformly dispersed, and any method can be used as a blending method. A representative example is a method of melt-kneading at a temperature of 200 to 350°C using a known melt mixer such as a single-screw or twin-screw extruder, a Banbury mixer, a kneader, or a mixing roll. Each component may be mixed together in advance and then melt-kneaded. The moisture adhering to each component is preferably small, and it is desirable to dry the components in advance, but it is not necessary to dry all the components.

[0035] As an example of a preferred manufacturing method, the method of feeding the thermoplastic polyester elastomer (B), layered clay mineral (C), and crystallization promoter (D) to the melt kneading extruder may be to feed the mixture of the polyethylene terephthalate resin (A) with the thermoplastic polyester elastomer (B), layered clay mineral (C), crystallization promoter (D), and release agent (E) all at once from the main hopper, but it is preferable to feed the thermoplastic polyester elastomer (B) separately from the main hopper in order to stabilize the blending amount. It is preferable to feed the layered clay mineral (C) from the middle of the extruder with a side feeder in order to stabilize the dispersibility and blending amount, and it is more preferable to feed it downstream of the extruder as much as possible. It is also preferable to feed the crystallization promoter (D) from the upstream of the extruder with a liquid addition pump in order to stabilize the dispersibility and blending amount.

[0036] The polyester resin composition of the present invention may be prepared by melt-kneading the thermoplastic polyester elastomer (B), the layered clay mineral (C), the crystallization accelerator (D), and the release agent (E) at a high concentration with the polyethylene terephthalate-based resin (A) by the above-mentioned method, and then feeding the resulting pellet-blended mixture with the polyethylene terephthalate-based resin (A) to an injection molding machine in the subsequent injection molding process.

[0037] The polyester resin composition of the present invention can be injection molded to form the molded article of the present invention. The polyester resin composition of the present invention can produce a molded article that is small (for example, the mass of the obtained molded article is about 15 g or less, preferably 7 g or less, more preferably 2 g or less) and has excellent releasability and flexibility while suppressing mold contamination. In addition, the molded article obtained by molding the polyester resin composition of the present invention can shorten the molding cycle and has excellent dimensional stability in a high-temperature environment. In addition, by using it for small molded objects such as buttons, hooks (also called snaps), zippers, and fastening rings in products such as clothing, carpets, and car mats made of polyethylene terephthalate fibers, it is possible to achieve mono-materialization of the product. EXAMPLES

[0038] The present invention will be specifically described below with reference to examples. 1. Evaluation Methodology (1) Formability Using a bar flow length measurement mold 20 mm wide and 1.0 mm thick, the flow length was measured under molding conditions of resin temperature 270°C, mold temperature 140°C, injection speed 40 mm / sec, and injection pressure 100 MPa. Flow lengths of 145 mm or more were evaluated as ○, those of 130 mm or more but less than 145 mm as △, and those less than 130 mm as ×. The molding machine used was the FANUC ROBOSHOT S-2000iB.

[0039] (2) Releasability (part 1) The test specimens were rectangular pieces measuring 13.0 mm wide, 125.0 mm long, and 1.6 mm thick, and were molded using the above molding machine under molding conditions of a resin temperature of 270°C and a mold temperature of 140°C. Those with an average cooling time of less than 15 seconds over 20 shots were rated as O, those between 15 and 17 seconds as △, and those over 18 seconds as X. The mass of the evaluated molded product was approximately 3.6 g.

[0040] (3) Releasability (part 2) The test specimen shape was a cylindrical molded product with a diameter of 20.0 mm and a thickness of 2.5 mm, and a 32-cavity mold for evaluating mold releasability with a submarine gate was used, and molding conditions were a resin temperature of 270°C, a mold temperature of 140°C, and a cooling time of 15 seconds. 20 shots were molded using the above molding machine, and those with less than 4 molded products remaining in the mold were rated as O, those with 4 to 7 molded products as △, and those with 7 or more molded products as ×. The mass of the evaluated molded product was approximately 1.1 g.

[0041] (4) Shape stability The test specimens were rectangular pieces measuring 13.0 mm in width, 125.0 mm in length, and 1.6 mm in thickness. The molding conditions were a resin temperature of 270°C and a mold temperature of 140°C. The ejector pin extrusion marks were observed when the test specimens were molded using the above molding machine. If no deformation was observed, the mark was marked ○, and if deformation was observed, the mark was marked ×.

[0042] (5)Flexibility The test pieces were molded in the form of rectangular pieces measuring 13.0 mm in width, 125.0 mm in length, and 1.6 mm in thickness using the above molding machine under molding conditions of a resin temperature of 270° C. and a mold temperature of 140° C. The bending strain of the molded pieces was measured, and a bending strain of 15% or more was evaluated as ◯, a bending strain of 10% or more but less than 15% was evaluated as △, and a bending strain of less than 10% was evaluated as ×. The bending test was performed using a Shimadzu Autograph AG2000. The test speed was 2 mm / min.

[0043] (6) Mold contamination Using the above molding machine, a rectangular molded specimen having a width of 13.0 mm, a length of 125.0 mm, and a thickness of 1.6 mm was molded continuously for 100 shots under molding conditions of a resin temperature of 270° C. and a mold temperature of 140° C. Thereafter, the mold was visually inspected for any adhesions, with a circle indicating no adhesions and a cross indicating adhesions.

[0044] (7) Dimensional stability Molded products with test piece dimensions of 60.0 mm x 60.0 mm x 2.0 mm (ISO 294-3 type D2) were molded using the above molding machine under molding conditions of a resin temperature of 270° C. and a mold temperature of 140° C. The molded products were left to stand in a 100° C. environment for 3 hours, and the flow direction dimensional change rate compared to the dimensions before standing was evaluated as ◯ if it was less than 0.7%, △ if it was 0.7% to 1.2%, and × if it exceeded 1.2%. The dimension measuring device used was an image dimension measuring device IM-8000 manufactured by Keyence Corporation.

[0045] 2. Raw materials The blend compositions used in the examples and comparative examples are shown below. (A-1) Polyethylene terephthalate resin: Unitika "XO-4063" homotype, intrinsic viscosity = 0.60 (A-2) Polyethylene terephthalate resin: "MA-2103" manufactured by Unitika Ltd., homotype, intrinsic viscosity = 0.70 (A-3) Polyethylene terephthalate resin: Unitika "SA-1206") Homotype, intrinsic viscosity = 1.10 (A-4) Polyethylene terephthalate resin: Unitika SA-8339P copolymer type, intrinsic viscosity = 1.10 (A-5) Polyethylene terephthalate resin: Unitika SA-863JP copolymer type, intrinsic viscosity = 1.18

[0046] (B-1) Thermoplastic polyester elastomer; "Hytrel 4047N" manufactured by Toray Celanese Co., Ltd. (B-2) Thermoplastic polyester elastomer; "Hytrel 4777" manufactured by Toray Celanese Co., Ltd. (B-3) Ethylene-glycidyl methacrylate copolymer: "Bondfast" manufactured by Sumitomo Chemical Co., Ltd.

[0047] (C-1) Talc; "MS" manufactured by Nippon Talc Co., Ltd., average particle size 14 μm (C-2) Mica: "B-82" manufactured by Yamaguchi Mica Co., Ltd., average particle size 180 μm

[0048] (D-1) Crystallization accelerator: Tri(caprylic / capric)glycerol, "Actor M-1" manufactured by Riken Vitamin Co., Ltd. (D-2) Crystallization accelerator: Glycerol fatty acid ester surfactant "Chirabazol VR-01" manufactured by Taiyo Kagaku Co., Ltd.

[0049] (E-1) Release agent: Paraffin wax, manufactured by Nippon Seiro Co., Ltd., "PW-155" (E-2) Release agent; Erucic acid amide, NOF Corp. "Alflow P-10" (E-3) Release agent; synthetic wax "FT115" manufactured by Nippon Seiro Co., Ltd.

[0050] Example 1 In a twin-screw extruder set at a resin temperature of 270°C, a screw rotation of 250 rpm, and a discharge rate of 20 kg / hour, 100 parts by mass of polyethylene terephthalate resin (A-1) and 0.5 parts by mass of release agent (E-1) were dry-blended and then charged from the main hopper, and 8.0 parts by mass of thermoplastic polyester elastomer (B-1) were also charged from the main hopper by a separate feeder. 3.0 parts by mass of crystallization accelerator (D-1) were fed from the upstream of the extruder by a liquid addition pump, and 4.0 parts by mass of layered clay mineral (C-1) were fed from the downstream of the extruder by a side feeder, melt-kneaded, extruded into strands from a die, cooled, pelletized, and polyester resin composition pellets were obtained. Each of the obtained pellets was dried in a 100°C vacuum dryer for 8 hours or more, and then molded and evaluated using the method described in the evaluation method. The evaluation results are shown in Table 1.

[0051] [Table 1]

[0052] Examples 2 to 18 A polyester resin composition was prepared, molded, and evaluated in the same manner as in Example 1, except that (A) to (E) were mixed in the combinations and amounts of raw materials shown in Table 1 or Table 2. The evaluation results are shown in Table 1 or Table 2.

[0053] [Table 2]

[0054] Example 19 In a twin-screw extruder set at a resin temperature of 270°C, a screw rotation of 250 rpm, and a discharge rate of 20 kg / hour, 100 parts by mass of polyethylene terephthalate resin (A-1) and 6.6 parts by mass of release agent (E-1) were dry-blended, and then charged from the main hopper, and 105.3 parts by mass of thermoplastic polyester elastomer (B-1) were also charged from the main hopper by a separate feeder. 13.0 parts by mass of crystallization accelerator (D-1) were fed from the upstream of the extruder by a liquid addition pump, and 17.3 parts by mass of layered clay mineral (C-1) were fed from the downstream of the extruder by a side feeder, melt-kneaded, extruded into strands from a die, cooled, pelletized, and obtained high-concentration polyester resin composition pellets. The obtained pellets were dried in a 100°C vacuum dryer for 8 hours or more. Then, 100 parts by mass of polyethylene terephthalate resin (A-1) and 25 parts by mass of high-concentration polyester resin composition pellets were blended to obtain a resin composition having the same composition as in Example 1. The evaluation results were the same as in Example 1 and were good.

[0055] Comparative Examples 1 to 9 Polyester resin compositions were prepared, molded, and evaluated in the same manner as in Example 1, except that the polyethylene terephthalate resin (A), thermoplastic polyester elastomer (B) or ethylene-glycidyl methacrylate copolymer, layered clay mineral (C), crystallization accelerator (D), and release agent (E) were mixed in the combinations and amounts of raw materials shown in Table 3. The evaluation results are shown in Table 3.

[0056] [Table 3]

[0057] The polyester resin compositions of Examples 1 to 19 exhibited excellent results in all of moldability, releasability, shape stability, flexibility, mold contamination, and dimensional stability.

[0058] The polyester resin composition of Comparative Example 1 had a low content of the thermoplastic polyester elastomer (B), and therefore showed little effect in improving toughness and was poor in flexibility.

[0059] The polyester resin composition of Comparative Example 2 had a high content of the thermoplastic polyester elastomer (B), and therefore had reduced hardness, poor shape stability and dimensional stability, and was also poor in terms of mold contamination.

[0060] In the polyester resin composition of Comparative Example 3, an ethylene-glycidyl methacrylate copolymer was used instead of the thermoplastic polyester elastomer (B), and therefore the compatibility with the polyethylene terephthalate resin was deteriorated, and the composition was inferior in terms of releasability, shape stability, dimensional stability, flexibility, and mold contamination.

[0061] The polyester resin composition of Comparative Example 4 had a low content of the layered clay mineral (C), and therefore showed poor releasability, shape stability and dimensional stability.

[0062] The polyester resin composition of Comparative Example 5 had a high content of the layered clay mineral (C), and therefore showed poor flexibility.

[0063] The polyester resin composition of Comparative Example 6 had a low content of the crystallization accelerator (D), and therefore was inferior in releasability, shape stability, and flexibility.

[0064] The polyester resin composition of Comparative Example 7 had a high content of the crystallization accelerator (D), and therefore showed poor mold contamination properties.

[0065] The polyester resin composition of Comparative Example 8 had a low content of the release agent (E), and therefore the results showed that the releasability and shape stability were poor.

[0066] The polyester resin composition of Comparative Example 9 had a high content of the mold release agent (E), and therefore showed poor mold contamination properties.

Claims

1. A polyester resin composition comprising: 100 parts by mass of a polyethylene terephthalate resin (A); 1.0 to 12.5 parts by mass of a thermoplastic polyester elastomer (B); 0.5 to 6.2 parts by mass of a layered clay mineral (C); 0.2 to 5.0 parts by mass of a crystallization promoter (D); and 0.1 to 1.0 part by mass of a release agent (E).

2. 2. The polyester resin composition according to claim 1, wherein the polyethylene terephthalate resin (A) has an intrinsic viscosity of 0.65 to 1.

15.

3. A molded article comprising the polyester resin composition according to claim 1 or 2.

4. The molded article according to claim 3, having a mass of 15 g or less.

5. A button, hook, fastener or fixing ring produced by molding the polyester resin composition according to claim 1 or 2.

6. Use of the button, hook, fastener or fixing ring according to claim 5 on a textile product made of polyethylene terephthalate-based fibers.

7. A textile product made of polyethylene terephthalate-based fibers, having the button, hook, fastener or fixing ring according to claim 5.

Citation Information

Patent Citations

  • Molding material for button

    JP1998007812A